The genera of Chrysomelinae (Coleoptera: Chrysomelidae) in Costa Rica - Wills Flowers, R. (2004)
Keys in Spanish and English are given for the genera of Chrysomelinae known from Costa Rica. For each genus, a list of species compiled from collections in the University of Costa Rica, the National Biodiversity Institute, and the entomological literature is presented. The genus Planagetes Chevrolat 1843 is recorded for the first time from Central America, and the genus Leptinotarsa Stål 1858 is synonymized with Stilodes Chevrolat 1843.